2004
DOI: 10.1007/s00441-004-0899-1
|View full text |Cite
|
Sign up to set email alerts
|

Polarized endocytosis and transcytosis in the hypothalamic tanycytes of the rat

Abstract: Four types of tanycytes can be distinguished in the rat hypothalamus: alpha(1) and alpha(2) tanycytes establish an anatomical link between the ventricular cerebrospinal fluid (CSF) and the arcuate nucleus, whereas beta(1) and beta2 tanycytes establish a link between CSF and portal blood. Endocytosis and transcytosis in these cells have been investigated by (1) immunocytochemistry with antibodies against molecular markers of the endocytotic and transcytotic pathways; (2) the administration of wheat germ aggluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0
13

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 63 publications
(96 reference statements)
4
76
0
13
Order By: Relevance
“…The observation that tanycytes endocytose substances from the CSF and transport them down their basal processes supports this hypothesis (Peruzzo et al 2004).…”
mentioning
confidence: 74%
“…The observation that tanycytes endocytose substances from the CSF and transport them down their basal processes supports this hypothesis (Peruzzo et al 2004).…”
mentioning
confidence: 74%
“…This has led to a debate about how the diffusion of substances from the median eminence could be restricted. In a series of studies addressing this question it was found that horseradish peroxidase (HRP) injected into either the cisterna magna or the third ventricle, quickly entered the perivascular spaces around the portal vessels in the external zone of the median eminence but no diffusion into the SEZ was observed (Peruzzo et al, 2004). The organisation of the b-tanycytes and the distribution of HRP suggested that the b1-tanycytes limit the dorsal diffusion in the median eminence and that the b2-tanycytes limit the D) or AgRP-immunoreactivity (red in E) did not take up OHSt (blue).…”
Section: Discussionmentioning
confidence: 98%
“…New data is emerging, suggesting an active role of tanycytes, cells lining the third ventricle, in controlling the movement of blood-borne molecules to the CSF and also from the CSF to the arcuate nucleus (28,38). It is tempting to speculate that chronically increased plasma ASP may lead to increased central ASP (as with insulin and leptin), and if so, this could induce a similar state of ASP resistance, as is demonstrated with insulin resistance and leptin resistance.…”
Section: Discussionmentioning
confidence: 99%